Beyond the Civil War Hospital : The Rhetoric of Healing and Democratization in Northern Reconstruction Writing, 1861–1882 /: The Rhetoric of Healing and Democratization in Northern Reconstruction Writing, 1861–1882. (2018) - Twelbeck, Kirsten
No abstract available